Analisis Program Literasi Terhadap Kemampuan Membaca Siswa di SDN 2 Bandorasawetan - Agustin, Dhina Aulia; Salam, Dudung Abdu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the implementation of literacy programs and their impact on students' reading skills at SDN 2 Bandorasawetan. The study uses a qualitative approach with a case study design. The research subjects were third-grade students, teachers, and the principal. Data were collected through observation of literacy activities, interviews with teachers and students, and documentation in the form of activity records and school facilities. Data analysis was carried out through data reduction, data presentation, and conclusion drawing using triangulation techniques to ensure data validity. The results showed that the literacy program had a positive effect on improving students' reading skills. The success of the program was supported by the implementation of a 15-minute reading activity every Wednesday using various techniques, the availability of supporting facilities such as libraries and reading corners, and the active involvement of the entire school community. However, several obstacles were also found, namely the low reading interest of some students, gaps in basic reading skills, and limited support from outside the school environment, especially from parents. These findings emphasize the importance of collaboration between schools and families in optimizing the success of literacy programs.